Standard on-the-job training program of corporate information technology - Alfonso, Armida Salamat (University of the Philippines Diliman, 2012)
Training provides people with key knowledge and skills needed to perform tasks effectively. Training can be used to create positive attitude and work habit especially from students undergoing On-the-job training (OJT). OJT is one of the most used training methodologies in any industry. It focuses on the acquisition of skills that students can use under normal working conditions. It is low in cost since it does not require expensive training materials to conduct the training. OJT should be focused on performing actual tasks at the workplace while developing good working habits for beginners. OJT is normally unstructured thus there are times important information or tasks are not discussed or covered properly. Traditional OJT is inconsistent because it relies solely on the experienced employee to provide training on what she/he thinks is necessary for the organization. This special project aims to combine both structured and traditional training methods to create a standard training program for Corporate Information Technology, division of United Laboratories, Inc. The organization, United Laboratories, Inc. (UNILAB), offers OJT programs to deserving students depending on the undergraduate course and required hours. UNILAB is a regional healthcare company with leading presence in Asia. Many of its products have become top brands in Indonesia, Thailand, Malaysia, Singapore, Hong Kong, Vietnam and Myanmar. UNILAB has a global network of strategic alliances delivering a steady stream of innovative products and technology. UNILAB is the most dominant provider of over-the-counter pharmaceuticals in the Philippines and is a massive, top echelon corporate identity. Corporate Information Technology (CIT) is a division of Unilab that supports corporate initiatives in terms of software, hardware and technology requirements. CIT aims to provide students with a formidable training ground, thru OJT program, as they complete the school requirement of practical experiences in real job scenarios. Though the intention of the division is clear some limitations hinder CIT to provide the best training possible for students. Among the limitations are the lack of formal documentation that makes life easy for trainers-trainees since there are certain norms and procedures that needs to be followed. Another limitation is the lack of standard OJT program that maximizes and showcases the potentials of OJTs. This special project aims to standardize the training program given to all OJTs. It includes framework, process flow and templates that are beneficial to the completion of required training hours. This study is focused not only on the technical aspect of the training but also the development of soft skills of students. It is really important that trainees should be accustomed with proper working habits since it is one of the factors that makes them successful in their chosen career. The author also proposed some of templates that can be useful in assessing and evaluating trainees as well as the content of the program for future enhancements. The author recommended possible enhancements on the proposed standard program which include CIT's pro-active role in partnering with technical schools and train 20 percent of their top students. It is likewise a venue for strengthening CIT's relationship with technical schools and look for potential source for new skills and talents.